Powder containing bridge structure, preparation method of powder, application of powder in anti-darkness liquid foundation and product
By using powders containing bridge structures in anti-dust foundation, the problems of darkening makeup and insufficient skin applicability are solved, and better makeup durability and applicability are achieved.
Patent Information
- Application Number
- CN202411787314.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-14
AI Technical Summary
Existing anti-darkening liquid foundations are difficult to fundamentally solve the problem of darkening makeup, and are not suitable for different skin types, which can easily lead to skin problems or unstable makeup.
The bridge structure powder is used to prepare anti-dusting liquid foundation liquid by mixing submicron polymer spheres and coloring agents, using surface modifiers and deposition of surface gloss treatment agents. .
This technology effectively improves the dispersion and adhesion of powder in oily media with low polarity, reduces the shrinkage and breakage of liquid foundation, extends the retention time of makeup, significantly improves the anti-dullness effect, and is suitable for Various skin types.
Smart Images

Figure CN119424222A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cosmetics, and in particular relates to a powder containing a bridge structure, a preparation method thereof, and an application thereof in an anti-dullness foundation liquid and a product thereof. Background Art
[0002] As consumers' demands for liquid foundations diversify and their makeup techniques improve, liquid foundations are gradually becoming more multifunctional. In addition to the basic functions of concealing blemishes and modifying skin tone, they also incorporate multiple functions such as anti-dullness, makeup lasting, and adapting to dry or oily skin to meet the needs of different consumers. As one of the sub-segments, anti-dullness liquid foundations are also constantly being segmented and deepened to meet the needs of specific consumers.
[0003] As a niche area in the cosmetics market, anti-dullness liquid foundation is gradually receiving more and more attention and research and development. In order to meet consumers' pursuit of perfect makeup, major cosmetics brands continue to launch anti-dullness liquid foundation products with innovative technologies. However, although there are many anti-dullness liquid foundations on the market, there is still a lack of a technical solution that can fundamentally solve the problem of darkening makeup. The main reason for darkening makeup is the drastic change in the brightness or color difference of the makeup, and the loss of balance between the glossiness and refractive index of the makeup effect. This phenomenon is usually caused by the invasion of oil secreted by the skin into the powder, resulting in a change in the refractive index of the powder, and the destruction of the film-forming agent film by sebum, resulting in mottled makeup and powder aggregation, which ultimately leads to dull makeup.
[0004] Secondly, the degree of dispersion of the powder will directly affect the color development effect of the toner, thereby affecting the color. This is related to the dispersion ability of the toner, the particle size of the powder, the selection of the treatment agent, the treatment process, etc., and is also related to the selection of oils and fats in the formula system. The better the compatibility of the toner with the oils and fats in the formula, the more complete the dispersion of the toner. On the contrary, when the compatibility of the toner with the oils and fats in the system is poor, the dispersion of the toner is reduced, the color will appear dull and easily lead to dullness.
[0005] In addition, factors such as the secretion of sebum and sweat, and light exposure can also cause dullness after applying foundation.
[0006] There are some problems with the anti-dullness foundations currently on the market, which limit their effectiveness and the people they are suitable for. For example, some products rely on the accumulation of film formers to achieve anti-dullness effects, but this often leads to skin problems such as acne, dryness, and cracks. For another example, some products control oil secretion by adding a large amount of oil-absorbing powder. Although this method can achieve the effect of oil control, it is not friendly to dry skin, which limits its applicability to the crowd. Finally, some products improve the film-forming speed and makeup effect by adding a large amount of non-volatile oil or polar oil, but this often leads to a rapid dissolution of makeup, and it is impossible to keep the makeup intact and fresh for a long time.
[0007] Therefore, it is particularly important to develop an anti-dullness foundation that can effectively solve the problem of darkening makeup, is suitable for all skin types, and does not cause skin problems. Such a product can not only meet consumers' pursuit of perfect makeup, but also enhance the market competitiveness of cosmetics brands and promote the development of the entire cosmetics industry. Summary of the invention
[0008] In order to solve the above problems, the present invention provides a powder containing a bridge structure, a preparation method thereof, and an application and product of the powder in an anti-dullness foundation liquid.
[0009] In one aspect, the present invention provides a powder containing a bridge structure.
[0010] Specifically, the powder includes: submicron polymer spheres, colorants, powder modifiers, surface gloss treatment agents and antioxidants, and a bridge structure is formed on the surface of the powder; the mass ratio of the surface gloss treatment agent, powder modifier and antioxidant is 5-40:0.1-7:0.1-7.
[0011] More specifically, the submicron polymer spheres are composed of HDI / trimethylol hexyl lactone cross-linked polymer and silica. As long as they meet INCI requirements of HDI / trimethylol hexyl lactone cross-linked polymer and silica, they can be used to prepare bridge structure powders.
[0012] Preferably, the mass ratio of the surface gloss treatment agent, the powder modifier and the antioxidant is 25-40:2-7:0.1-7.
[0013] More specifically, the colorant includes, but is not limited to, at least one of titanium dioxide, aluminum hydroxide, cerium oxide and / or zinc oxide.
[0014] Preferably, the colorant includes titanium dioxide, aluminum hydroxide, cerium oxide and zinc oxide.
[0015] In certain specific embodiments of the present invention, in the colorant, the mass ratio of titanium dioxide, aluminum hydroxide, cerium oxide and zinc oxide is 40-65:0.1-2:0.1-7:0.1-5.
[0016] More specifically, the powder modifier includes but is not limited to: at least one of triethoxyoctylsilane, perfluorooctyltriethoxysilane, hydrogenated polydimethylsiloxane and / or polymethylsiloxane.
[0017] Preferably, the powder modifier is polymethylsiloxane.
[0018] More specifically, the surface gloss treatment agent includes, but is not limited to, at least one of boron nitride, synthetic fluorphlogopite, mica, lauroyl lysine and / or bismuth oxychloride.
[0019] Preferably, the surface gloss treatment agent is bismuth oxychloride.
[0020] More specifically, the antioxidant includes at least one of nano titanium dioxide, zinc oxide, chemical sunscreens and / or skin conditioners.
[0021] Preferably, the antioxidant is zinc oxide.
[0022] In another aspect, the present invention provides a method for preparing a powder containing a bridge structure.
[0023] Specifically, the preparation method comprises the following steps:
[0024] (1) mixing submicron polymer spheres with a colorant to obtain spherical powders having a core-shell structure;
[0025] (2) using a surface modifier to treat the spherical powder surface to complete the hydrophobic and oleophobic layer coating;
[0026] (3) Depositing a surface gloss treatment agent on the surface of the spherical powder coated with the hydrophobic and oleophobic layer to obtain a bridge structure powder.
[0027] More specifically, in step (1), the mass ratio of the submicron polymer spheres to the colorant is 0.1-7:40-66.77.
[0028] More specifically, the colorant includes: titanium dioxide, aluminum hydroxide, cerium oxide and zinc oxide, and the mass ratio of the four is 40-65:0.1-2:0.1-7:0.1-5.
[0029] More specifically, in step (2), the surface treatment method is: mechanical force-chemical method.
[0030] In certain specific embodiments of the present invention, the specific steps of the mechanical force-chemical method are:
[0031] a. Add the spherical powder obtained in step (1) to the powder machine, adjust the speed to 500-1200r / min, and process for 5-10min;
[0032] b. Place the crushed powder in a heating electric furnace at a temperature of 50-110 degrees for 5-10 minutes to allow the silicone to combine with the powder and complete the hydrophobic and oleophobic coating.
[0033] Preferably, in step (a), the rotation speed is 800-1200 r / min, and the treatment time is 8-10 min.
[0034] Preferably, in step (b), the temperature is 70-110° C. and the treatment time is 5-10 min.
[0035] More specifically, in step (3), the surface gloss treatment agent is added in an amount of 5-40% for complete immersion.
[0036] In certain specific embodiments of the present invention, the step of depositing the surface gloss treatment agent is:
[0037] 1) heating the hydrophobic and oleophobic coated microsphere particles to 50-110 degrees to form a stable slurry;
[0038] 2) The surface gloss treatment agent is formed into fine powder through high-speed shearing (speed: 300-500r / min, 3-5min);
[0039] 3) Mix the microsphere particle slurry and the surface gloss treatment powder at 70-110°C and 300-500r / min.
[0040] Preferably, in step 1), the microsphere particles are heated to 85-110°C.
[0041] In another aspect, the present invention provides use of the above powder or the powder obtained by the above preparation method in preparing an anti-dullness liquid foundation.
[0042] In another aspect, the present invention provides a product containing bridge structure powder.
[0043] Specifically, the product includes the above powder or the powder obtained according to the above preparation method.
[0044] More specifically, the product is an anti-dullness liquid foundation.
[0045] Preferably, the anti-dullness liquid foundation further comprises: water, a film former, an emulsifier, an oil phase component and a matrix component.
[0046] Further preferably, the anti-dullness liquid foundation comprises the following components by weight percentage: 1-25% of bridge structure powder; 0.1-15% of film former; 0.1-5% of emulsifier; 5-25% of oil phase component; and the remainder is matrix component and water.
[0047] In certain specific embodiments of the present invention, the steps for preparing the anti-dullness liquid foundation are:
[0048] S1: The bridge structure powder, emulsifier, color powder and non-volatile oil phase components are ground evenly with a high-pressure homogenizer to obtain phase A;
[0049] S2: Add the film-forming agent, volatile oil phase components and thickener into an emulsifying pot, and homogenize and disperse them until there are no particles to obtain phase B;
[0050] S3: Mix phase A and phase B in an emulsifier and homogenize and disperse them until uniform to obtain an oil phase;
[0051] S4: Put water, polyol and functional additives into the water phase pot, stir and disperse until transparent, and obtain the water phase;
[0052] S5: The water phase is pumped into an emulsifying pot under stirring to be fully emulsified and homogenized, and raw materials such as preservatives and flavors are added to prepare an anti-dullness liquid foundation containing a bridge-structured powder.
[0053] Compared with the prior art, the present invention has the following advantages:
[0054] The powder containing the bridge structure prepared by the present invention can be well dispersed in an oil medium with low polarity, has good adhesion on the skin, low friction, has the effects of resistance to sweat and oil secreted by the skin, etc., is retained on the skin for a long time, the powder is evenly dispersed, has a soft texture, can reduce product shrinkage and breakage, and can reduce the phenomenon of mottled or dark makeup due to liquid foundation on the skin. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 The present invention is a preparation process of powders containing bridge structures.
[0056] Figure 2 This is an electron microscope image of the powder containing a bridge structure in Example 1. DETAILED DESCRIPTION
[0057] The present invention will be further described in detail below in conjunction with specific examples. The following examples are not intended to limit the present invention, but are only intended to illustrate the present invention. The experimental methods used in the following examples are generally conventional, unless otherwise specified, and the materials, reagents, etc. used in the following examples are commercially available, unless otherwise specified.
[0058] Example 1
[0059] In this example, the amount of each substance used is shown in Table 1.
[0060] Table 1
[0061]
[0062]
[0063] The preparation steps of bridge powder are as follows:
[0064] (1) Submicron high molecular polymer spheres (composed of silica and HDI, purchased from Guangzhou Boyu New Materials Co., Ltd., batch number: YRFE0806007) were mixed with colorants (titanium dioxide, aluminum hydroxide, cerium oxide and zinc oxide) and fully immersed so that the surface negative charge of the colorant was combined with the submicron high molecular polymer spheres through electrostatic action to form spherical powders with a core-shell structure.
[0065] (2) Adding polymethylsiloxane as a surface modifier to treat the surface of the powder filler, adding the powder filler to a powder pulverizer by a mechanochemical method, with a rotation speed of 1200 r / min for 10 min, using a heating electric furnace, maintaining 90° C., and treating for 8 min to allow the silicone to combine with the powder.
[0066] At this time, one end of the surface modifier molecule is a polar group, which can be physically adsorbed or chemically reacted with the powder surface to connect together, while the lipophilic group (long hydrocarbon chain) at the other end forms a physical entanglement or chemical reaction with the microsphere powder, which is manifested as a layer of alkyl chains formed on the outer layer of the microsphere powder, reducing the hydrophilicity of TiO2 and reducing the flocculation of TiO2 particles.
[0067] (3) Finally, bismuth oxychloride is deposited on the surface of the microspheres:
[0068] The microsphere particles were heated to 98°C to form a stable slurry.
[0069] Bismuth oxychloride was formed into fine powder by high-speed shearing (speed: 500 r / min, 3 min);
[0070] At 90°C and 400r / min, bismuth oxychloride and titanium dioxide slurry were mixed.
[0071] In this step, bismuth chloride ions react with certain groups (such as hydroxyl groups) on the surface of titanium dioxide particles to form bismuth oxychloride, which is deposited on the surface of titanium dioxide particles. The amount of bismuth oxychloride added is 5-40% of the total amount of bridge powder treated) and combines with the long hydrocarbon chain end of the surface modifier to build a "molecular bridge" between the inorganic filler and the organic polymer, coupling all the substances.
[0072] Preparation process see Figure 1 The electron microscope image of the prepared bridge structure powder is shown in Figure 2 .
[0073] The preparation method of anti-dullness liquid foundation is as follows:
[0074] (1) The bridge structure powder, emulsifier, color powder and non-volatile oil phase components are ground uniformly using a high-pressure homogenizer to obtain phase A;
[0075] (2) Add the film-forming agent, volatile oil phase components, and thickener into an emulsifying pot and homogenize and disperse them until there are no particles to obtain phase B;
[0076] (3) Mixing phase A and phase B in an emulsifying pot and homogenizing and dispersing them until uniform, to obtain an oil phase;
[0077] (4) putting water, polyol and functional additive into a water phase pot, stirring and dispersing until transparent, to obtain a water phase;
[0078] (5) Finally, the aqueous phase is added to an emulsifying pot under stirring to be fully emulsified and homogenized, and raw materials such as preservatives and flavors are added to prepare an anti-dullness liquid foundation containing a bridge structure powder.
[0079] Example 2
[0080] In this example, the amount of each substance used is shown in Table 2.
[0081] Table 2
[0082]
[0083] The preparation steps of bridge powder are as follows:
[0084] (1) Submicron polymer spheres (composed of silica and HDI, purchased from Guangzhou Boyu New Materials Co., Ltd., batch number: YRFE0806007) were mixed with colorants (titanium dioxide, aluminum hydroxide, cerium oxide and zinc oxide).
[0085] (2) Adding polymethylsiloxane as a surface modifier to treat the surface of the powder filler, adding the powder filler to a powder pulverizer by a mechanochemical method, rotating at a speed of 1000 r / min for 10 min, heating in an electric furnace at a temperature of 110 degrees, and treating for 5 min to combine the silicone with the powder.
[0086] (3) Finally, bismuth oxychloride is deposited on the surface of the microspheres:
[0087] The microsphere particles were heated to 110°C to form a stable slurry.
[0088] Bismuth oxychloride was formed into fine powder by high-speed shearing (rotation speed: 400 r / min, 4 min);
[0089] At 110 degrees and 500 r / min, mix bismuth oxychloride with titanium dioxide slurry.
[0090] The preparation method of the anti-dullness liquid foundation is the same as that of Example 1.
[0091] Example 3
[0092] The amount of each component is shown in Table 3.
[0093] Table 3
[0094]
[0095]
[0096] The preparation steps of bridge powder are as follows:
[0097] (1) Submicron polymer spheres (composed of silica and HDI, purchased from Guangzhou Boyu New Materials Co., Ltd., batch number: YRFE0806007) were mixed with colorants (titanium dioxide, aluminum hydroxide, cerium oxide and zinc oxide).
[0098] (2) Adding polymethylsiloxane as a surface modifier to treat the surface of the powder filler, adding the powder filler to a powder pulverizer by a mechanochemical method, rotating at a speed of 800 r / min for 8 min, heating in an electric furnace at a temperature of 70 degrees, and treating for 10 min to combine the silicone with the powder.
[0099] (3) Finally, bismuth oxychloride is deposited on the surface of the microspheres:
[0100] The microsphere particles were heated to 85°C to form a stable slurry.
[0101] Bismuth oxychloride was formed into fine powder by high-speed shearing (speed: 300 r / min, 5 min);
[0102] At 70 degrees and 500 r / min, mix bismuth oxychloride with titanium dioxide slurry.
[0103] The preparation method of the anti-dullness liquid foundation is the same as that of Example 1.
[0104] Example 4
[0105] The difference from Example 1 is that the dosage of each component is different, and the specific dosage is shown in Table 4.
[0106] Table 4
[0107]
[0108] Comparative Example 1
[0109] The difference from Example 1 is that during the preparation of the bridge structure, the mass ratio of the surface gloss treatment agent, the powder modifier and the antioxidant is 30:7:7
[0110] Comparative Example 2
[0111] The difference from Example 1 is that during the preparation of the bridge structure, the mass ratio of the surface gloss treatment agent, the powder modifier and the antioxidant is 40:7:0.1.
[0112] Comparative Example 3
[0113] The difference from Example 1 is that the amount of bridge structure powder added is 30 g, the amount of water added is reduced, and the final mass of the total system is maintained at 100 g.
[0114] Comparative Example 4
[0115] The difference from Example 1 is that the amount of bridge structure powder added is 0.5 g, and the amount of water added is increased to maintain the final mass of the total system at 100 g.
[0116] Experimental Example 1
[0117] A color spectrum desktop spectrophotometer (model: CS-821N) was used to test the color difference change (anti-dullness effect) of liquid foundation.
[0118] Apply the liquid foundation evenly on the glass plate with an applicator, test it with a desktop spectrophotometer within 2 minutes, record the standard sample values L*, a*, b*, and retest after 1h, 2h, 4h, and 8h, and record dL*, da*, db*. At this time, the machine will give the value of dE*ab. When dE*ab<2, it means that the liquid foundation has an anti-dullness effect. The experimental results are shown in Table 5.
[0119] Table 5
[0120]
[0121] By testing the color difference results of 1h, 2h, 4h and 8h with a desktop spectrophotometer, it was found that the anti-dulling liquid foundation containing a bridge structure powder in Example 1-4 has a good anti-dulling effect, in the liquid foundation of Comparative Examples 1-2, the distribution ratio of each component of the powder containing a bridge structure is not within the scope of protection required by the present application, and the anti-dulling effect of the liquid foundation is significantly reduced, in the liquid foundation prepared in Comparative Example 3, the content of the powder containing a bridge structure exceeds 25%, and the anti-dulling effect of the liquid foundation is significantly reduced, in the liquid foundation prepared in Comparative Example 4, the content of the powder containing a bridge structure is less than 1%, and the anti-dulling effect of the liquid foundation is significantly reduced.
[0122] Experimental Example 2
[0123] VISIA-CR was used to evaluate the dullness and durability of makeup. Test subjects: 18 volunteers were selected, all female, aged 20-35 years old, healthy, without skin diseases and allergies. Finally, 18 subjects completed the test, including 8 with dry skin, 6 with oily skin, and 4 with mixed skin. Use facial cleanser to clean the whole face, apply the same moisturizing lotion, sit in a constant temperature and humidity room for at least 20 minutes, during which time you cannot drink water or beverages, expose your whole face, and keep relaxed. The makeup artist applied liquid foundation to the subjects, and then took VISIA-CR photos. After 4 hours and 8 hours, VISIA-CR photos were taken again. After the test, the VISIA-CR device drew a before-and-after comparison conclusion. Laboratory experts conducted a before-and-after comparison of dullness, makeup removal, and mottled spots, and evaluated and scored the makeup: the makeup removal degree score was 0-9 (0: none; 1: very slight; 2: slight; 3: relatively slight; 4: somewhat obvious; 5: obvious; 6: very obvious; 7: relatively serious; 8: serious; 9: very serious). The experimental results are shown in Table 6.
[0124] Table 6
[0125]
[0126]
[0127] The comparison of makeup before and after using the VISIA-CR device showed that the average value of the makeup lasting effect of Example 1 was between slight makeup coming off and relatively slight makeup coming off, the average value of the makeup lasting effect of Example 2 was between slight makeup coming off and relatively slight makeup coming off, the average value of the makeup lasting effect of Example 3 was between relatively slight makeup coming off and a little obvious makeup coming off, and the average value of the makeup lasting effect of Example 4 was between a little obvious makeup coming off and obvious makeup coming off.
[0128] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A powder containing a bridge structure, characterized in that: The powder comprises: submicron polymer spheres, colorants, powder modifiers, surface gloss treatment agents and antioxidants, and a bridge structure is formed on the surface of the powder; the mass ratio of the surface gloss treatment agent, powder modifier and antioxidant is 5-40:0.1-7:0.1-7.
2. The powder according to claim 1, characterized in that The colorant includes: at least one of titanium dioxide, aluminum hydroxide, cerium oxide or zinc oxide; The powder modifier comprises: at least one of triethoxyoctylsilane, perfluorooctyltriethoxysilane, hydrogenated polydimethylsiloxane or polymethylsiloxane; The surface gloss treatment agent comprises at least one of boron nitride, synthetic fluorphlogopite, mica, lauroyl lysine, and bismuth oxychloride; The antioxidant comprises at least one of nano titanium dioxide, zinc oxide, chemical sunscreen and skin conditioner.
3. A method for preparing a powder containing a bridge structure, characterized in that: The following steps are involved: (1) mixing submicron polymer spheres with a colorant to obtain spherical powders having a core-shell structure; (2) using a surface modifier to treat the spherical powder surface to complete the hydrophobic and oleophobic layer coating; (3) Depositing a surface gloss treatment agent on the surface of the spherical powder coated with the hydrophobic and oleophobic layer.
4. The preparation method according to claim 3, characterized in that: In step (2), the surface treatment method is: mechanical force-chemical method.
5. The preparation method according to claim 4, characterized in that: In step (3), the amount of the surface gloss treatment agent added is 5-40% by weight.
6. Use of the powder according to any one of claims 1 to 2 and / or the powder prepared by the preparation method according to any one of claims 3 to 5 in preparing an anti-dullness liquid foundation.
7. A product, characterized in that The product comprises the powder according to any one of claims 1 to 2 and / or the powder prepared by the preparation method according to any one of claims 3 to 5.
8. The product according to claim 7, characterized in that The product is an anti-dullness liquid foundation, which comprises the following components: water, bridge structure powder, film former, emulsifier, oil phase component and matrix component.
9. The product according to claim 8, characterized in that The anti-dullness liquid foundation comprises the following components by weight percentage: 1-25% of bridge structure powder; 0.1-15% of film former; 0.1-5% of emulsifier; 5-25% of oil phase component; and the remainder is matrix component and water.
10. The product according to any one of claims 8-9, characterized in that The preparation steps of the anti-dullness liquid foundation are as follows: S1: The bridge structure powder, emulsifier, color powder and non-volatile oil phase components are ground evenly with a high-pressure homogenizer to obtain phase A; S2: Add the film-forming agent, volatile oil phase components and thickener into an emulsifying pot, and homogenize and disperse them until there are no particles to obtain phase B; S3: Mix phase A and phase B in an emulsifier and homogenize and disperse them until uniform to obtain an oil phase; S4: Put water, polyol and functional additives into the water phase pot, stir and disperse until transparent, and obtain the water phase; S5: The water phase is pumped into an emulsifying pot under stirring to be fully emulsified and homogenized, and raw materials such as preservatives and flavors are added to prepare an anti-dullness liquid foundation containing a bridge-structured powder.